The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4236/ojpsych.2018.82014
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing the Neural Correlates of Binge-Eating Disorder with Lisdexamfetamine: A Case Report and Literature Review

Abstract: The brain regions associated with binge-eating disorder (BED) and those targeted by Lisdexamfetamine (LDX) overlap. The present paper reviews the psychobehavioural and neuropharmacological mechanisms at play in BED and compulsive eating behaviours, along with the mechanisms of action LDX is thought to play. We present one case of chronic BED and highlight the EEG scans pre-and post-LDX treatment. The normalization of the patient's electroencephalogy (EEG) activity associated with BED after LDX supports theoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 25 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…These studies reported percentage improvements in self-reported symptoms in most of the participants, but a worsening of symptoms after LDX treatment in 2 of 25 cases (Guerdjikova et al, 2019). The results of Brucar et al (2018) did not include a symptom improvement outcome. Fleck et al (2019) reported that LDX improved BED symptoms using the CGI, YBOCS-BE, and BES.…”
Section: Global Binge-eating Symptomsmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies reported percentage improvements in self-reported symptoms in most of the participants, but a worsening of symptoms after LDX treatment in 2 of 25 cases (Guerdjikova et al, 2019). The results of Brucar et al (2018) did not include a symptom improvement outcome. Fleck et al (2019) reported that LDX improved BED symptoms using the CGI, YBOCS-BE, and BES.…”
Section: Global Binge-eating Symptomsmentioning
confidence: 99%
“…Of the 14 clinical articles, four (Guerdjikova et al, 2016;Hudson et al, 2017;McElroy et al, 2015a;McElroy et al, 2015c) reported the results of a randomised controlled trial (RCT), and one reported the results of two RCTs (McElroy et al, 2016a). Three articles reported the results of open-label studies (Fleck et al, 2019;Gasior et al, 2017;Hudson et al, 2017), two were case reports (Brucar et al, 2018;Srivastava et al, 2019), two were retrospective medical record reviews (Guerdjikova et al, 2019;Keshen & Helson, 2017) and three were secondary data analyses (Kornstein et al, 2019;McElroy et al, 2017;McElroy et al, 2016b).…”
Section: Clinical Studiesmentioning
confidence: 99%
See 3 more Smart Citations